THE IMPLEMENTATION OF PICTURE SERIES IN TEACHING NARRATIVE READING TEXT - Rifka S. Mbirongi; Muhammad Ihsan; Ana Kuliahana (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2022)
This research aimed at finding out the implementation of picture series in teaching narrative reading text to the eight grade students of MTs al-Khairaat Uemalingku Ampana. This research was qualitative research, the subjects of this research were teachers and students. The data collection methods employed in this study were observation, interviews, and documentation. The data sources used in this study were primary data and secondary data. Data analysis techniques used were data reduction, data presentation, and data verification. The result of this research showed that the implementation of Picture Series in Teaching Narrative Reading Text to the Eight grade Students of MTs al-Khairaat Uemalingku Ampana consists of the following steps: firstly, the teacher trained the students to think and directed them to find answer to problems by playing drawing games. Secondly, the teacher explained the material deeply, such as the step to write narrative text. Thirdly, the teacher distributed some random pictures to the students to short the pictures into a logical sequence and to find out the difference in the learning outcomes that had been achieved by students in learning narrative text. The learning evaluation was carried out at the end of the lesson.